Electrochemical printing of calcium alginate/gelatin hydrogel. (10th August 2018) - Taira, Noriko; Ino, Kosuke; Robert, Jordan; Shiku, Hitoshi
Abstract: Here, we report the electrochemical printing of calcium-alginate (Ca-alginate)/gelatin hydrogel. The printing process involves placing an electrode within or above a gelatin hydrogel containing sodium alginate and CaCO3 particles. Owing to acidification resulting from water electrolysis at the electrode, Ca 2+ is released from the CaCO3 particles, resulting in the formation of a Ca-alginate hydrogel within the gelatin. By scanning a probe electrode or by placing patterned electrodes in the desired locations, the hydrogel formation reaction could be made to occur at any location, with the formed Ca-alginate hydrogel being trapped within the gelatin, which acted as a supporting scaffold. Upon heating, the untreated gelatin melted, yielding patterned Ca-alginate/gelatin hydrogels. In addition, mammalian cells could be cultured successfully within the hydrogel. Finally, by stacking layers of the patterned hydrogel sequentially, three-dimensional (3D) hydrogel printing could be achieved. This method of electrochemical hydrogel printing has significant potential for use in the construction of 3D tissue organs.